Cost-effective DNA extraction method optimized for high yield and long fragments from coastal sediments - Leopold Matthys; Eléonord Mayissah Moungues; Anaëlle Genève; Virginie Sanial; Benjamin Misson; Elisabeth Navarro (PLoS ONE, 2026)
Efficient DNA extraction from coastal sediments is a critical step for studying microbial communities, especially when targeting high-molecular-weight DNA for long-read sequencing. Here, we compare a cost-effective laboratory-made (LM) extraction method with two widely used commercial kits: Qiagen DNEasy™ PowerSoil™ Pro (PSP) and PowerMax™ Soil (PM). In sandy, low-organic-matter sediments, the LM method consistently produced higher DNA yields – up to 13 times more than the commercial kits – and longer DNA fragments (up to 4-fold), likely due to its enzymatic lysis approach. It was also the only method that successfully amplified the 18S rRNA gene in sufficient quantity to enable downstream sequencing in certain samples. While prokaryotic diversity metrics were largely similar across methods, we observed differences in eukaryotic richness that were likely influenced by the amount of sediment processed. This demonstrates the higher importance of sample amount when assessing microeukaryotic diversity. Despite these differences, the LM method gave reproducible results and recovered taxa that were less frequently detected by commercial kits. In terms of cost, the LM method is significantly cheaper per sample than commercial alternatives, despite a higher starting cost. Although it requires more hands-on time, this trade-off may be worthwhile for large-scale studies and developing countries. Overall, the LM method is a robust and economical option, particularly suited for sandy or low-biomass sediments, and for studies requiring high-quality DNA. These results underline the importance of choosing and validating extraction protocols based on both the sediment type and the study’s goals.